Segmented Market of Indonesian Coffee Exports to International Market: RFM Approach - Rondhi, Mohammad; Nugroho, Hari; Soetriono, Soetriono; Mori, Yasuhiro (Directorate of Research and Community Services, 2024)
This study aims to determine the characteristics of coffee products in the international market. Data is collected from coffee product export transaction data from 2011-2021, Indonesia Statistic. Export data were selected based on the Harmony system (HS) code of coffee and its derivatives. The analysis method used is RFM (Recency, Frequency, Monetary) Analysis. The results show that there are 12 categories of coffee products exported to 90 countries divided into 9 regions/zones respectively. Coffee export products with the highest interest are arabica WIB (not roasted and not decaffeinated wet-processed Arabica coffee beans) or Robusta OIB (unroasted, with caffeine) coffee. Then the best markets for coffee products exported by Indonesia are the United States, Japan, Malaysia, Germany, Egypt, Georgia, Australia, United Arab Emirate, and Ecuador. The second-best exported coffee product is roasted coffee, with caffeine, unground that being imported Malaysia, China, and New Zealand. The two categories contribute 98% of export volume of Indonesia’s exported coffee and 78% frequency. The study confirms that the choice of coffee and its derivative products in importing countries is influenced by purchase timing, frequency, and funds used. In addition, purchasing factors are also influenced by the characteristics of consumers and processed industries in these importing countries